Dos Litterae de concesión de indulgencias del siglo XIV inéditas otorgadas al Monasterio de San Isidoro - Domínguez Sánchez, Santiago (Estudios humanísticos. Geografía, historia y arte, 1993)
The following article brings up two unpublished documents of 14th century issued by a great number of archbishops and bishops met in Council by means of which several spiritual graces are granted to parishioners of "San Isidoro de León". A simple paleographic and diplomatic study is also included.